- The type of the intellectual hero and his spiritual and moral potential in Ilyas Yesenberlin's novel “The Battle” - Ibrayeva, Zh.B.; Baidrakhmanov, D.K. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article addresses issues concerning the history of literature and theoretical concepts. It presents material on the genesis of the Kazakh intelligentsia, defines its term and meaning in contemporary interpretation; reviews the works of Kazakh literary scholars, delving into the origins of national self-consciousness and the history of the Kazakh intelligentsia's formation. An analysis of Ilyas Yesenberlin’s novel is conducted in light of the stated topic, identifying two main types of intellectual heroes. A significant feature of Yesenberlin's works is the affirmation of the subjective source of socially significant life values through the intense, dynamic spiritual and practical activity of the intellectual hero. This aspect highlights the relevance of the study, which is closely tied to spiritual values, worldview, and the role and mission of the intelligentsia. The subject of this study is the type of intellectual hero. The object is the hero's spiritual and moral potential in the novel. The goal is to identify the type of intellectual hero and their spiritual and moral potential in Ilyas Yesenberlin’s novel. The article emphasizes the practical significance of its materials and their potential use in teaching disciplines on 20 th-century Kazakh literature, specialized seminars on literary regional studies, and more.